Fruit nutritional composition, antioxidant and biochemical profiling of diverse tomato (Solanum lycopersicum L.) genetic resource - Raza, Bushra; Hameed, Amjad; Saleem, Muhammad Yussouf (Frontiers in Plant Science, 2022)
Tomato is the second most important vegetable crop consumed globally, by the virtue of its antioxidant-rich phytochemicals and bioactive compounds. Identifying genotypes with high antioxidant capacities and nutritionally rich phytochemicals is imperative for improving human health. The present study aimed to analyze 21 antioxidant and nutritional compounds in 93 geographically diverse, high yielding, better quality, stress tolerant tomato genotypes (hybrids, parental lines, inbred lines, and advanced lines). Significant variation (p < 0.05) was detected for investigated traits among the tested genotypes. Principal component analysis revealed the hybrids NIAB-Jauhar, Iron-lady F1, NBH-258, Ahmar F1, NIAB-Gohar, the parents H-24, B-25, AVTO1080, Astra and AVTO1003, as well as the lines LBR-17, AVTO1315, AVTO1311 and Lyp-1 revealed superior performance for the traits such as chlorophylls, lycopene, total carotenoids, total antioxidant capacity, total oxidant status, protease, alpha-amylase and total flavonoid content. Whereas the hybrids Surkhail F1, NBH-204, NBH-229, NBH-151, NBH-196, NBH-152, NBH-261, NBH-228, NIAB-Jauhar, NBH-256 and NBH-255, the lines 21354, AVTO1315, Newcherry, LA4097, AVTO1311 and UAF-1 together with the parents Naqeeb, NCEBR-5, M-82 and LBR-10 exhibited significant contribution to the traits such as total soluble sugars, reducing sugars, malondialdehyde, ascorbic a.cid, esterase, peroxidase and superoxide dismutase. Moreover, the semi-determinate and determinate tomato genotypes together with the categories parents and lines with positive factor scores of 3.184, 0.015, 0.325 and 0.186 in PC- I, exhibited better performance for the trait such as total chlorophylls, lycopene, total carotenoids, total oxidant status, protease, alpha-amylase, total antioxidant capacity, esterase and total flavonoid content. Whereas again the semi-determinate and indeterminate tomato genotypes along with the category hybrids with positive factor scores of 2.619, 0.252 and 0.114 in PC- II, exhibited better performance for the traits such as total soluble sugars, reducing sugars, chlorophyll b, Malondialdehyde content, ascorbic acid, superoxide dismutase and peroxidase. Hybrid vigor was observed in the hybrids for investigated traits. The aforementioned tomato genotypes showing outstanding performance in the respective traits can be exploited in the breeding programs to improve nutritional quality of tomato that can further improve human health.